Observations of Polar Bear Predatory Behaviour toward Caribou - Brook, Ryan K.; Richardson, Evan S. (ARCTIC, 2002)
A polar bear (Ursus maritimus) was observed unsuccessfully stalking and chasing caribou (Rangifer tarandus) in western Hudson Bay. Before chasing the caribou, the polar bear appeared to make use of wind direction and vegetation cover in order to move close to them. While there have been very few documented cases of the two species interacting, our observations indicate that polar bears will stalk and chase caribou. On a observé un ours polaire (Ursus maritimus) traquer et poursuivre sans succès le caribou (Rangifer tarandus) dans l'ouest de la baie d'Hudson. Avant de se lancer dans sa poursuite, l'ours polaire semblait s'aider de la direction du vent et du couvert végétal pour s'approcher des animaux. Bien que très peu de cas d'interaction des deux espèces aient été documentés, nos observations révèlent qu'en réalité les ours polaires traquent et poursuivent le caribou.